Preliminary study of the algae of Pucallpa near Loreto - Montoya T., Haydée (1974)
This paper reports about 17 genera with 27 species of fresh-water algae collected at Pucallpa, Department of Loreto. The following species of CYANOPHYTA and CHLOROPHYTA are new records to the Peruvian flora: Chroococcus minor, Microspora tumidula, Cylindrocystis brebissonii, Closterium baillyanum, Closterium johnnsonii, Euostrum luetkemuellerii, Euastrum paulense, Cosmarium contractum, Casmorium punctulotum, Desmidium optogonum and Phymatodocis nordstedtiona.